The Tempest [videorecording (DVD)] - Messina, Cedric; Gorrie, John; Shakespeare, William, 1564-1616 (The Shakespeare plays, 1987)
This play revolves around an enchanted island, an exiled duke, young lovers and a framework of conspiracy as they affected dramatic and emotional romances.